Prevention of Bradycardia by Atropine Sulfate During Urological Laparoscopic Surgery: A Randomized Controlled Trial - Aghamohammadi, Homayun; Mehrabi, Sadrollah; Mohammad Ali Beigi, Faramarz (Urology Journal, 2009)
Introduction: Cardiac arrhythmias are a well-recognized complication of anesthesia for laparoscopy. The aim of this study was to evaluate the efficacy of atropine sulfate for prevention of bradyarrhythmia during laparoscopic surgery. Materials and Methods: Sixty-four candidates for urological laparoscopic surgery were randomly assigned into 2 groups to receive either atropine sulfate or hypertonic saline solution (as placebo), intravenously 3 minutes before induction of anesthesia for the laparoscopic procedure. Then, all of the patients underwent anesthesia intravenous sodium thiopental and atracurium, followed by isoflurane or halothane inhalation. Heart rate and blood pressure were recorded preoperatively in the recovery room, preoperatively in the operation room, after induction of anesthesia, after induction of pneumoperitoneum, and postoperatively. Results: A significant decreasing trend was seen in the heart rates during the operation in patients without atropine sulfate. Nine of 32 patients (28.1%) in this group developed bradycardia, while none of the patients with atropine sulfate prophylaxis had bradycardia perioperatively (P < .001). The mean decreases in systolic blood pressure between induction of anesthesia and pneumoperitoneum were 15.7 ± 10.2 mm Hg in group 1 and 23.5 ± 9.8 mm Hg in group 2 (P < .001). The mean decreases in diastolic blood pressure between these two measurements were 8.7 ± 5.2 mm Hg in group 1 compared to 12.1 ± 6.2 mm Hg in group 2 (P = .001). Conclusion: This study suggests that routine prophylaxis with an anticholinergic agent might be helpful in prevention of sinus bradycardia during urological laparoscopic surgery.